Absorption, distribution, metabolic fate, and elimination of pefloxacin mesylate in mice, rats, dogs, monkeys, and humans. - Montay, G (1984)
Pefloxacin mesylate is well absorbed by the oral route. The antimicrobial activity in dog, cynomolgus monkey, and human plasma was essentially due to unchanged drug which respectively accounted for 64, 94, and 84% of the total activity (ratios derived from relative area under the curve [AUC] values). Half-lives ranged from 1.9 h in mice to 8.6 h in humans. Protein binding was weak, about 20% in plasma. Except in brain, concentrations in most of the organs and tissues tested in rats and dogs were higher than the plasma levels. Microbiological activity in urine was mainly due to pefloxacin and norfloxacin, the N-desmethyl metabolite. The norfloxacin/pefloxacin ratios were 0 in mice, ca. 1 in rats and dogs, 1.6 in cynomolgus monkeys, and 2.3 in humans. The principal urinary compounds were unchanged drug in mice, pefloxacin glucuronide and pefloxacin N-oxide in rats and dogs, norfloxacin and pefloxacin in monkeys, and pefloxacin N-oxide and norfloxacin in humans. The urinary recovery of identified metabolites was 29.5% of the dose in mice, 37.8% in rats, 36.3% in dogs, 26.5% in monkeys, and 58.9% in humans. Biliary excretion occurred and was extensive in rats and dogs, mainly as a glucuronide conjugate of the drug. In rat and human bile, the main active compound was unchanged pefloxacin.